Analysis of Z-Shaped Microstrip Bandpass Filter at Ku Band - Govardhani.Immadi, M.Venkata Narayana, A. Navya, M. S. V. S. L. Sreejasree, D. Sai Krishna, V. Sri Sindhu (International Journal of Advanced Science and Technology, 2020)
A Z-shaped planar microstrip band pass filter is designed using An soft HFSS software at the Ku band of the frequency range of 12-18 GHz. This filter consists of a substrate of material FR4_epoxy with a thickness of 1.6mm and ground and patch with the boundary condition of perfect E. We use microstrip filter as it reduces the size of the filter while it maintains the same performance levels as waveguide filters which are bulky.